Research on solution to expand the bandwidth of X-band waveguide bandpass filter applied in passive radar - Lưu Đức Thọ; Lương Văn Trình; Nguyễn Công Oai (Journal of Military Science and Technology, 2024)
Currently, ultra-high frequency filters are widely used in many different fields. In radar systems, filters play an important role in the transmit-receive line, but ensuring that the filter works in a wide frequency range and has low loss is a complex problem. In this paper, the authors present the results of research and design of a waveguide bandpass filter working in the frequency range of 8 to 12 GHz (X-band). The results of the analysis of the operating principle, calculation and simulation on CST 2019 software show that the bandpass filter operates in a wide frequency range, meeting the requirements of passive radar stations.